2001
DOI: 10.1309/425h-nw4w-xc9a-005h
|View full text |Cite
|
Sign up to set email alerts
|

Consultative (Expert) Second Opinions in Soft Tissue Pathology

Abstract: We reviewed 500 consecutive soft tissue lesions referred for expert consultation to determine types of lesions and/or situations in which major discrepancies occur. Of 266 cases (53.2%) accompanied by a diagnosis, essential agreement with the second opinion was noted in 68%, minor discrepancy in 7%, and major discrepancy in 25%. The 65 major discrepancies were distributed proportionally to the referring sources and could be divided into 4 groups: benign mesenchymal lesions diagnosed as sarcomas (45%), sarcomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
3
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 10 publications
6
77
3
8
Order By: Relevance
“…Because all these were conducted in private, there was no formal record concerning the details of this consultation practice among the pathology society in Taiwan. Because expert consultation is one of the methods to improve patient safety, the Department of Health, Executive Yuan, Taiwan, Republic of China had funded the Taiwan There were several reports in the literature concerning extradepartmental anatomic pathology expert consultation [2][3][4][5][6][7][8][9]. Most of them were based on single organ or single institutional experience [2,[5][6][7][8][9], data of nationwide consultation was only available in one article [3].…”
Section: Introductionmentioning
confidence: 99%
“…Because all these were conducted in private, there was no formal record concerning the details of this consultation practice among the pathology society in Taiwan. Because expert consultation is one of the methods to improve patient safety, the Department of Health, Executive Yuan, Taiwan, Republic of China had funded the Taiwan There were several reports in the literature concerning extradepartmental anatomic pathology expert consultation [2][3][4][5][6][7][8][9]. Most of them were based on single organ or single institutional experience [2,[5][6][7][8][9], data of nationwide consultation was only available in one article [3].…”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11][12][13][14][15] Several of these factors contribute to establishing a precise diagnosis, but the pathologist's knowledge and experience remain the essential factors in interpretive diagnosis. Although numerous studies have shown that case reviews help detect interpretive diagnostic errors, there have been no efforts to formalize this practice as a strategy to reduce errors.…”
mentioning
confidence: 99%
“…Verschiedene In Deutschland werden von 1200 Pathologen pro Jahr von einem lediglich zwei Weichteilsarkome diagnostiziert. In einem Viertel der FĂ€lle muss eine Korrektur der PrimĂ€rdiagnose erfolgen [1]; wird der Tumor von einem Referenzzentrum nachbegutachtet, stiegt diese Quote sogar auf 70 % an [14].…”
Section: Tumoren Des Retroperitoneumsunclassified